Comparison of Enoxaparin and Unfractionated Heparin on Thrombin Generation in Acute Coronary Syndromes without ST-Segment Elevation - Salvioni, Alessandro; Casilli, Francesco; Assanelli, Emilio; Grazi, Marco; Marenzi, Giancarlo; Guazzi, Maurizio D. (Thrombosis and Haemostasis, 2001)
Recent clinical trials have demonstrated a better ability of low-molecular-weight heparin, compared to unfractionated heparin, in reducing ischemic cardiac events in patients with acute coronary syndromes without ST-segment elevation. No data are available concerning the in-vivo comparison of enoxaparin and unfractionated heparin on thrombin generation in patients with unstable angina or non-Q-wave myocardial infarction. We measured the plasma levels of prothrombin fragment 1+2 (a marker of prothrombin activation) and thrombin/anti-thrombin complex (a marker of thrombin generation) in 45 patients with non ST-elevation acute coronary syndromes who were randomized to receive enoxaparin, 3000 IU anti-Xa as an i. v. bolus, followed by 70 IU anti-Xa/Kg every 8 h for 3 days (23 pts, Group 1) or a bolus of 100 IU/kg of unfractionated heparin followed by infusion for 3 days titrated to maintain the aPTT between 70 and 90 s (22 pts, Group 2). Plasma levels of prothrombin fragment 1+2 reduced significantly at 3rd h of treatment in both groups (–42% in Group 1 and –45% in Group 2), reached the lowest plasma concentration at the 24th h and exhibited a slight increase at the 72nd h; no differences were observed between the two groups at any time points. Plasma thrombin/antithrombin complex levels had a similar behaviour: reduced markedly in both groups at the 3rd h (–52% in Group 1 and –46% in Group 2), remained lower during the first two days and slightly rose at 72nd h. No differences between the two groups in plasma levels of this marker were apparent during drug infusion. In Group 1 the aPTT did not show significant changes; in Group 2 the mean value of aPTT doubled the basal value at any time point of determination. Both enoxaparin and unfractionated heparin produced a marked and similar reduction of thrombin generation. Other unknown mechanisms might explain the different clinical effects of the two heparins.
Keywords: Acute coronary syndromes; low-molecular-weight heparin; thrombin generation